2013
DOI: 10.5603/fhc.2013.0023
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of dental pulp in human upper first premolar teeth based on immunohistochemical and morphometric examinations

Abstract: Teeth extracted for orthodontic reasons are commonly considered as healthy. Therefore, it is possible to examine structure of the dental pulp can be fully recognized and how it is affected by malocclusion. The aim of the study was to evaluate by immunohistochemistry (IHC) and morphometry dental pulp in human upper first premolar teeth extracted for orthodontic reasons. The material comprised 36 teeth of 20 patients in the age range 16-26 years. By the use of IHC markers the presence of immunocompetent cells (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…This has also been reported by Tomaszewska et al, 2013 who observed that the cell-free zone may often be absent while the cell-rich zone was always present but with some modification to its cellular elements (Tomaszewska, Miskowiak, Matthews-Brzozowska & Wierzbicki, 2013). The reduction of the subodontoblasts with age will also have an effect on the tooth's ability to function in response to tooth injury.…”
Section: Discussionsupporting
confidence: 54%
“…This has also been reported by Tomaszewska et al, 2013 who observed that the cell-free zone may often be absent while the cell-rich zone was always present but with some modification to its cellular elements (Tomaszewska, Miskowiak, Matthews-Brzozowska & Wierzbicki, 2013). The reduction of the subodontoblasts with age will also have an effect on the tooth's ability to function in response to tooth injury.…”
Section: Discussionsupporting
confidence: 54%
“…) and 14–51 μm (Tomaszewska et al . ). Given the positive correlation between vessel diameter and flow rate, it can be deduced that the blood flow velocities of the pulp arterioles, which are 10–50 μm in diameter, were approximately 0.1–2.0 cm s −1 .…”
Section: Discussionmentioning
confidence: 97%
“…Contact of hydrogen peroxide with the dental enamel causes mineral loss, thus increasing its porosity, which increases diffusion of the bleaching agent into deeper areas of dentin and pulp tissue 20 . By histologic examination, some studies have reported that depending on the type of pulp irritability and potency, minor alterations such as reversible inflammatory reactions or even tissue degeneration may occur 3 , 21 , 25 . The presence of lymphocytes is common in these cases, characterizing the inflammatory process 8 , 21 .…”
Section: Discussionmentioning
confidence: 99%